Respiratory Physiology and Pathophysiology - Kerr, Carolyn L.; Teixeira-Neto, Francisco J. [UNESP] (Wiley, 2024)
Maintenance of adequate respiratory function is a principal requirement for safe anesthesia. The respiratory system is responsible for eliminating carbon dioxide (CO 2) via adjustments in alveolar ventilation per minute (V˙ A), and for transferring oxygen from the alveoli to mixed venous blood (pulmonary artery blood) at the pulmonary capillary level. This chapter aims to provide a review of respiratory physiology with emphasis on pathophysiological changes in respiratory function associated with sedation and general anesthesia in domestic species.
Keywords: alveolar; carbon dioxide; deadspace; hypercapnia; hypoxemia; Oxygen; oxygenation; oxyhemoglobin; perfusion; ventilation